Rigodon ; Pesticides ; A lasting image [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Focuses on Joseph "Erap" Estrada who settled down for vice president for Danding Cojuangco. Focuses on the "transformer candidates." Examines the issues behind the use of pesticides. Filipino photojournalists decided to compile their photos of Mt. Pinatubo and Zambales in a coffee table book. Profits from the sale of the book will be used to help rebuild the place.